Damage analysis of sandstone during the creep stage under the different levels of uniaxial stress using NMR measurements. Issue 3 (23rd November 2020) - Cheng, Hao; Zhou, Xiaoping; Pan, Xiaokang; Berto, Filippo
Abstract: In this paper, the nuclear magnetic resonance (NMR) measurements are carried out to evaluate the micro‐cracking characteristics of sandstones during the creep stage under the different levels of creep stresses. The variations in the parameters, including transverse relaxation time (T2 ) spectra distribution, percentage of the pore distribution, incremental value of porosity and ultrasonic P wave velocity are analysed. The results show that, during the creep stage, small pores in the rocks gradually evolve into large pores, resulting in an increase in damage of rocks. With the increase of the loading ratio, the increasing rate of porosity increases sharply, implying that the damage degree becomes more serious under the high loading ratio. When the loading ratio is larger than 0.7, the increasing rate of porosity and the decreasing rate of the P wave velocity both increases rapidly. During the creep stage, the relationship between micro‐crack and macro‐creep characteristics of rocks is established based on the analysis of the deformation and the porosity evolution during creep. It is found that, as the loading ratio increases, the increasing rate of porosity is linear with the creep strain. The NMR method offers a feasible option to identify micro‐cracking process of rocks during the creep stage, which can directly reflect the damage mechanism of rock caused by creep. The porosity of rocks is an effective parameter to evaluate the damage of rocks. The damage evolution of the specimen is highly anisotropic and is heavily related to the loading ratio during the creep stage. The relationship between the damage parameter and the loading ratio is exponential.